The problem of aggression : a proposal of measures of enforcement against violations of the Treaty for the Renunciation of War as an instrument of national policy (the Pact of Paris also known as Kellogg-Briand Pact) - Léon, Maurice (S.l. : s.n., 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Wereldoorlog 2; vredesakkoorden